Differences in diameter and thickness of the seminiferous tubules of male wistar rats (rattus norvegicus) after being exposed to e-cigarette smoke and conventional cigarettes - Atalya Riawani Iring; Etha Rambung; Hudi Winarso (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Electric cigarettes and conventional cigarettes have a detrimental effect on their users. Cigarettes contain ingredients that reduce the quality of male reproduction. Purpose: To determine the differences in diameter and thickness of the seminiferous tubules of male Wistar rats (rattus norvegicus) exposed to electric cigarettes compared to conventional cigarettes. Method: This research is a true experimental research in the laboratory using a post test-only control group design. The treatment group consisted of group K- as the negative control group, group K+ which was included in  the smoking chamber but not exposed to cigarette smoke, group P1 which was included in the smoking chamber  and exposed to electric cigarette smoke, group P2 which was included in the smoking chamber and exposed to  conventional cigarette smoke. The treatment was carried out for 30 days and then testicular samples were taken to calculate diameter and thickness of the seminiferous tubules. Data were analyzed with SPSS using descriptive statistics and One Way ANOVA and Kruskall Wall is tests. Results: There was a decrease in the diameter and thickness of the seminiferous tubules in the treatment group which was significantly different from the control group. The results of the LSD post hoc test for differences in seminiferous tubule diameter between groups P1 and P2 were p=0.72 > 0.05. The results of the Mann Whitney test showed that the difference in seminiferous tubule thickness between groups P1 and P2 was p=0.06 > 0.05.Conclusion: Exposure to electric and conventional cigarettes caused changes in the diameter and thickness of the seminiferous tubules from normal conditions. There was no significant difference in the impact of exposure to electric and conventional cigarettes, maybe because the damage they produced was not different.